Exploring Paranormal (Spiritual) Communication: An Analysis of the Spirit Box Communicator Mobile App - Aruku, Kalita; Omelagah, Godwin Ekunke; Ikangkang, Joseph; Inyali, Peter Ogar (ALSYSTECH Journal of Education Technology, 2025)
The fascination with the paranormal and the desire for communication with the unseen have transcended generations, giving rise to a plethora of tools and technologies aimed at facilitating contact with spiritual entities. Among these, the Spirit Box mobile app has emerged as a popular medium for enthusiasts and skeptics alike who seek to explore the realms of the unexplained. With a focus on the Spirit Box Communication app's user interface, working principles, and potential consequences for the investigation of paranormal occurrences, this article provides a thorough dissection of the program. By examining user feedback and case studies qualitatively, we shed light on the many user experiences related to the app and uncover the historical, cultural, psychological, and emotional aspects of paranormal participation. Along with analyzing the scientific viewpoint on spiritual connection and the difficulties in confirming subjective experiences in the paranormal realm, we also critically address possible objections and skepticism. Ultimately, this piece considers the wider consequences of mobile technology in the field of spiritual inquiry, taking into account how programs such as Spirit Box could affect society's beliefs about life after death, the place of spirituality in modern life, and the direction of mystical arts.